2022
DOI: 10.1038/s41420-022-01006-4
|View full text |Cite
|
Sign up to set email alerts
|

Mucin 21 confers resistance to apoptosis in an O-glycosylation-dependent manner

Abstract: Highly glycosylated mucins protect epithelial surfaces from external insults and are related to malignant behaviors of carcinoma cells. However, the importance of carbohydrate chains on mucins in the process of cellular protection is not fully understood. Here, we investigated the effect of human mucin-21 (MUC21) expression on the susceptibility to apoptosis. MUC21 transfection into HEK293 cells decreased the number of apoptotic cells in culture media containing etoposide or after ultraviolet light irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Furthermore, by knocking down β-galactoside α2-6-sialyltransferase ST6Gal-1, which catalyzes the addition of sialic acid to galactose, ovarian tumor cells gained cisplatin resistance [ 30 ]. Together with a recent study showing that the overexpression of human T-MUC21 and sialyl T-MUC21 confers anti-apoptotic properties to cells, whereas non-glycosylated MUC21 and Tn-MUC21 do not [ 11 ], these findings underscore the importance of glycoforms in the regulation of mucin function. The 1A4-1 and 18A11 mAbs will potentially be useful tools to elucidate this structure–function relationship in Muc21.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, by knocking down β-galactoside α2-6-sialyltransferase ST6Gal-1, which catalyzes the addition of sialic acid to galactose, ovarian tumor cells gained cisplatin resistance [ 30 ]. Together with a recent study showing that the overexpression of human T-MUC21 and sialyl T-MUC21 confers anti-apoptotic properties to cells, whereas non-glycosylated MUC21 and Tn-MUC21 do not [ 11 ], these findings underscore the importance of glycoforms in the regulation of mucin function. The 1A4-1 and 18A11 mAbs will potentially be useful tools to elucidate this structure–function relationship in Muc21.…”
Section: Discussionsupporting
confidence: 53%
“…Recent studies have shown that MUC21 acts a negative marker for epithelioid mesothelioma [ 9 ] and that MUC21 proteins with a specific glycosylation status may be involved in the progression of EGFR-mutated lung adenocarcinomas [ 10 ]. Finally, we reported that the expression of MUC21 confers resistance to apoptosis in an O -glycosylation-dependent manner, underscoring the glycoform-dependent functions of mucins [ 11 ]. Although monoclonal antibodies specific to several glycoforms of human MUC21 have been previously established, antibodies for mouse Muc21 have not been previously obtained.…”
Section: Introductionmentioning
confidence: 99%
“…One important aspect is that glycosylation is known to modulate the function of molecules involved in apoptosis [ 20 ]. We recently reported that Mucin 21 confers resistance to apoptosis in an O-glycosylation-dependent manner [ 21 ]. Another aspect is that the function of drug transporters is glycosylation-dependent [ 22 24 ], with studies showing that different glycans influence the sensitivity to different drugs through a variety of mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The latest research indicates that specific glycosylated MUC21 may be involved in the development of lung adenocarcinoma with EGFR mutations ( 22 ). In addition, the over-expression of human T-MUC21 and sialylated T-MUC21 confers cells with anti-apoptotic characteristics, whereas unglycosylated MUC21 and Tn-MUC21 do not possess this characteristic ( 37 , 38 ). These findings underscore the importance of glycosylation in regulating the function of mucins.…”
Section: Muc21-specific Glycoform Tumor Correlationsmentioning
confidence: 99%
“…Tian et al. discovered that the anti-apoptotic capability of CHO cells expressing O-glycosylated MUC21 increased, with the expression of T-MUC21 and sialylated T-MUC21 in these cells imparting an anti-apoptotic characteristic ( 37 ). Conversely, the expression of unmodified MUC21 or Tn-MUC21 did not endow these cells with an anti-apoptotic trait ( 37 ).…”
Section: Muc21 Regulates Cellular Functionsmentioning
confidence: 99%